Elements of planting design - Austin, Richard L. 4 0 16; 5 (New York : John Wiley & Sons, 2002)
Presents step-by-step planting design guidance for landscape architects, covering commercial and residential sites, technical and aesthetic aspects of design, and graphic techniques, and includes sample projects, study questions, and over three hundred illustrations.
Portions of this text were originally developed by the author as Designing with Plants and Designing the Natural Landscape, published in 1982 and 1984 by Van Nostrand Reinhold--Acknowledgments.
Includes bibliographical references (p. 171) and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Landscape gardening; 20; 2